Narrrative Form : Cause and Effect Dalam Menjelaskan Karakter Bu Darmi dalam Film Pendek Bu Darmi - Parawangsa, I Gusti Made Darma; Sitepu, Petrus Damiami (Universitas Bunda Mulia, 2024)
This study examines the concept of Narrative Form: Cause and Effect in describing the premise and character changes of Bu Darmi, as well as the arrangement of Narrative Film in Bu Darmi's short film. Additionally, the correlation between Narrative Form and Mise en Scene is explored. The study was conducted using a qualitative method with a descriptive approach, through in-depth observations of the theories applied to Bu Darmi's short film work. This text analyzes the use of Narrative Form in structuring a narrative, specifically in the Mise en Scene element, to demonstrate the Cause and Effect relationship that impacts character development and the influence of pressure on the main character. The research focuses on the Narrative Form elements, particularly the use of Cause and Effect to Effectively convey the character's transformation in Bu Darmi's short film. This writing aims to provide a deeper understanding of the theory of Narrative Form and Mise en Scene: Staging. The research specifically focuses on the Mise en Scene element, which is crucial in film. Narrative Form shapes the characters in a movie. The writing presents a comprehensive analysis of Bu Darmi's short film screenplay, with a focus on the protagonist's character development.